Kualitas Dan Daya Simpan Ikan Nila Dan Kakap Merah Menggunakan Daun Kecombrang Sebagai Pengawet Alami - KQOMARIYAH, NURUL, Dra. Titik Suryani, M.Sc (2016)
Tilapia and red snapper is one of marine resources commodity with economic value . the contains of tipia is, moisture content 81,4%, abu 1%, protein 18,8 %, fat 0,6 %), in 100 g (gram) meat of red snappercontains total fat 40 g, saturation fat 12,4 mg, MUFA (Monounsaturated fat) 6,4 mg, PUFA (Polyunsaturated fat) 21,2 mg, EPA 11 mg, DHA 117 mg, AA 38 mg, dan colestrol 21 mg. But,there are have hight risk to be damage and spoiled. The treatment can be prevented using natural preservative that kecombrang leaf. Contains in kecombrang leaf alkaloid,saponin, tanin, fenolik, flavonoid, triterpenoid, steroid, and glikosida inhibiting bacterial growth. The purposes of this research has to know quality and preservation tilapia and red snapper with concentration variation of kecombrang leaf extract . The study method using complete randomized of two factors. Factor 1 : kind of fishes, P1= tilapia, P2= red snapper, the second factor was concentration variation of kecombrang leaf extract, Q1= concentration of kecombrang leaf extract 20%, Q2= concentration of kecombrang leaf extract 30%, Q3= concentration of kecombrang leaf extract 40%. The result of research showed that the best preservation in P2Q3 treatment (red snapper with concentration of kecombrang leaf extract 40%) with amount of population bacetria 0,7x107 bacteria CFU / g, preservative until 18 hours.